Strategi dan Peluang dalam Pembelajaran Agama Islam melalui Pendekatan Multikultural di Sekolah - Fauzi, Ismail; Mangan, Asriyani Biti; Ma'ruf, Husein; Khasanah, Siti Nur (Lembaga Yasin AlSys, 2022)
In life, humans are required to always improve their knowledge and skills in order to keep up with the times and explore in improving their standard of living. Several ways that humans do in increasing their knowledge and skills are through education. The educational process carried out by humans is not only focused on seeking general and worldly knowledge but also religious knowledge. In religious science education, humans are not only taught about the science of worship, but also social science which aims to know and practice interactions between humans in life according to procedures according to religion. Every individual of man has various contrasting differences, be it his nature, character or actions, depending on where he was born and raised. And every human being also has differences in their way of life, beliefs and culture. While in Islamic religious science, humans were created by God from male and female and from various tribes and nations to get to know each other. In the course of human history, in interpreting the differences and diversity of humans in this world, a special field of science was formed to study the differences and diversity of mankind, namely through multicultural education. Multicultural education aims to appreciate, learn and appreciate the differences and diversity possessed by every human being who comes from various ethnic groups. In line with multicultural education, religious education, especially Islamic religious education, interprets a difference in every human being is to know each other and respect each difference. So that multicultural education and Islamic religious education cannot be separated in an effort as education taught through educational institutions.